Effect of brewer’s yeast or beta-glucan on breast milk supply following preterm birth: the BLOOM study – protocol for a multicentre randomised controlled trial - Luke E. Grzeskowiak; Alice R. Rumbold; Lauren Williams; Renee L. Kam; Wendy V. Ingman; Amy Keir; Kathryn A. Martinello; Lisa H. Amir (International Breastfeeding Journal, 2024)
Abstract Background Many individuals who experience preterm birth struggle with early breast milk supply, which can translate into suboptimal longer-term breastfeeding outcomes. Further investigations into the potential role of early non-pharmacological and pharmacological interventions in improving breast milk production soon after birth is growing. While natural galactagogues, such as brewer’s yeast, are widely perceived by women to be safer than pharmaceutical galactagogues and are taken by many women, evidence to support their efficacy is largely absent. The BLOOM study has been designed to determine the efficacy and safety of brewer’s yeast and beta-glucans, derived from Saccharomyces cerevisiae, when administered soon after birth for increasing early breast milk supply in mothers who have delivered preterm. Methods The BLOOM study is a multicentre, double-blinded, randomised controlled trial that will assess if brewer’s yeast or beta-glucan can increase early breast milk production following preterm birth. Target population are mothers of preterm infants born at less than 34 weeks’ gestation who intend to provide breast milk for their infant, are less than 72 h following birth and able to give informed consent. Participants will be randomly allocated into three parallel groups at 1:1:1 ratio (n = 33 per group) to receive either brewer’s yeast, beta-glucan or placebo capsules for seven days. The primary outcome is total expressed breast milk volume over a 24-hour period on day 7 of intervention. Participants and their infants will be followed until the infant reaches term corrected age or is discharged home from the neonatal unit (whichever occurs first). Discussion The use of brewer’s yeast as a galactagogue to enhance milk production is extremely common amongst breastfeeding mothers, however, there are no trials evaluating its efficacy and safety. This will be the first randomised controlled trial to evaluate the efficacy and safety of two commonly used galactagogues, brewer’s yeast and beta-glucan, compared with placebo in improving maternal breast milk supply following preterm birth. The trial will also evaluate whether early intervention with galactagogues soon after a preterm birth improves longer-term breastfeeding outcomes. Trial registration Australian and New Zealand Clinical Trials Registry ACTRN12622000968774 (registered on 8 July 2022) and UTN U1111-1278-8827.